Pemberdayaan Kelompok Remaja melalui Pelatihan Desain Grafis di Desa Prajegan, Sukorejo, Kabupaten Ponorogo - Musari, Fajar Sidik; Ahrori, Moh. Hazim; Sari, Dewi Yunita (Social Science Academic, 2024)
illage teenagers are an association where they are the object and play a role in carrying out events in Prajegan village. Graphic design is a communication process using visual elements, such as typography, photography and illustrations which are intended to create a perception of a message conveyed on social media. In general, graphic designers make extensive use of images, photos, symbols and various forms of language and visual elements. In this service activity we will help village teenagers develop their potential to get job opportunities in the design field to strengthen the economy and also their productivity. Graphic design training can provide basic graphic design skills to village teenagers to be able to create media publications in Prajegan village. The aim of this program is to provide knowledge about graphic design to village teenagers and village youth organizations, provide knowledge about coloring in making a design, change consumer behavior in teenagers regarding smartphone use, and build better relationships between teenagers. The method used for community mapping is the ABCD method. method by utilizing assets owned by local communities which are seen to support community empowerment activities, here we use the pixellab application for the training we hold.